Schematic idioms and cultural models - Stanojević, Mateusz-Milan (2007)
This paper combines the constructional approach to idioms (Fillmore et al. 1988) with an investigation of idiom motivation based on ICMs/cultural models (Lakoff 1987). We will compare the syntactic and semantic make-up of English constructions with the combination of components ?in ... eyes? and Croatian constructions with the combination of components ?u ... očima?. The aim is to show that these combinations are in fact schematic idioms with a relatively stable structure, depending on the ICM/cultural model motivating them. In order to show this, we analyzed a sample of these constructions from the BNC and the Croatian National Corpus. The analysis has confirmed that there are a limited number of cultural models motivating most expressions in both languages and that each model is associated with a particular schematic structure. For instance, the examples: (1) Staring up at him, she tried to read his own feelings in his eyes and couldn?t. (2) U njegovim je očima bilo mnogo saučešća. ?There was a lot of sympathy in his eyes.? belong to the eyes-as-the-reflection-of-the-soul model, and reflect the structure [(Vperceive/be) N/V/AdjATTITUDE in somebody?s eyes]. Results will be presented for three predominant cultural models (the physical model, the eyes-as-the-reflection-of-the-soul model and the seeing (perception) model) in the two languages. Comparison of Croatian and English has shown similarities (in cultural models, reflected in schematic constructions) and differences (in different elaborations of schematic usage patterns). Our results lead us to believe that other constructions with ?eyes? and ?oči? may exhibit similar characteristics, which may indicate that familiar pieces familiarly arranged may not be as semantically irregular as has been previously thought. References Fillmore, C. J., P. Kay and M. O?Connor. 1988. Regularity and idiomaticity in grammatical constructions: the case of let alone. Language 64: 501-538 Lakoff, G. 1987. Women, Fire, and Dangerous Things. The University of Chicago Press